Four days of bed rest increases intrinsic mitochondrial respiratory capacity in young healthy males. Issue 18 (17th September 2018) - Larsen, Steen; Lundby, Anne‐Kristine M.; Dandanell, Sune; Oberholzer, Laura; Keiser, Stefanie; Andersen, Andreas B.; Haider, Thomas; Lundby, Carsten
Abstract: Bed rest leads to impaired glucose tolerance. Whether this is linked to maladaptation's in skeletal muscle mitochondrial function and in particular to the level of reactive oxygen species (ROS) is at present unknown. The aim of this longitudinal study was to quantify skeletal muscle mitochondrial function (respiratory capacity and ROS production) together with glucose tolerance after 4 days of strict bed rest in healthy young male subjects ( n  =   14). Mitochondrial function was determined in permeabilized muscle fibers using high‐resolution respirometry and fluorometry, mitochondrial content (citrate synthase [CS] activity) and antioxidant protein expression levels were assessed in parallel to this. Glucose tolerance was determined by means of oral glucose tolerance tests. Intrinsic mitochondrial respiratory capacity was augmented after the bed rest period (CI + II P : 0.43 ± 0.12 vs. 0.55 ± 0.14 [pmol/sec/mg]/CS activity), due to a decreased CS activity (158 ± 39 vs. 129 ± 25 mU/mg dw.). No differences were observed in ROS production (per mg of tissue or when normalized to CS activity). Furthermore, the protein content for catalase was increased while superoxide dismutase and glutathione peroxidase remained unaffected. These findings were accompanied by an impaired glucose tolerance after the bed rest period (Matsuda index: 12 ± 6 vs. 9 ± 5). The change in intrinsic mitochondrial respiratory capacity could be an early indication in the development of impaired glucose tolerance. The increased catalase protein content might explain that no change was seen in ROS production after 4 days of bed rest. Whether these findings can be extrapolated to lifestyle‐dependent decrements in physical activity and the development of type‐2‐diabetes remains unknown. Abstract : Intrinsic mitochondrial respiratory capacity is increased after 4 days of bed rest.